Responsibility for war crimes in the activities of international criminal tribunals (Journal of actual problems of jurisprudence, 2022)
The main goal of this article is to research the legal issues of responsibility for war crimes in the activities of international criminal tribunals. The Nuremberg Tribunal also introduced a separate concept of “war crimes”, which is an important step in bringing war criminals to justice. It should be noted that the Nuremberg and subsequent tribunals are international both in terms of their legal source and in terms of their jurisdiction.The question of bringing to justice those responsible for war crimes raises not only scientific but also practical problems. These problems have become apparent in the work of the international criminal tribunals. Problems arise in the logistical, financial spheres, the search for the accused, evidence, collection of documents, etc. These issues are among these problems, but the main obstacle is the real support by states of the activities of these tribunals, the timely implementation of decisions and decisions of the tribunals. One of the common negative features of the tribunals in both the former Yugoslavia and Rwanda was that it was impossible to bring to justice those responsible for international crimes in a timely manner, and trials were lengthy. The International Criminal Tribunals for the Former Yugoslavia and Rwanda, which do not impose the death penalty, have a UN Security Council mandate, which distinguishes them from classical international tribunals established under an international treaty.Keywords: war crimes, tribunal, Nuremberg, Yugoslavia, Rwanda, jurisdiction, responsibility, UN General Assembly, UN Security Council, Geneva Conventions, Appeals Chamber, International Criminal Court.